The role of restrictive abortion laws on modern contraceptive use in Sub Saharan Africa - Kumbeni, Maxwell Tii; Bovbjerg, Marit L.; Harvey, S. Marie; Chi, Chunhuei; Luck, Jeff (PLOS global public health, 2025)
Previous evidence found that restrictive abortion laws were associated with high incidence of unsafe abortions and abortion-related complications. But few studies have assessed the association of restrictive abortion laws with contraceptive use patterns. Our study examined the role of restrictive abortion laws on contraceptive use among women in Sub Saharan Africa (SSA). We performed secondary data analysis using the most recent Demographic and Health Survey data along with the 2022 abortion law classification data from the Center for Reproductive Rights (CRR) for 31 countries in SSA. Based on CRR classification, abortion restriction was categorized into three, ordinal levels; broadly liberal, moderately restrictive, and highly-restrictive laws. We conducted multivariable, multilevel logistic regression analysis to estimate odds ratios (OR) and 95% confidence intervals (CI). The analysis also included multivariable imputation by chained equations to account for missing data. A weighted sample of 453,195 women of reproductive age (15–49 years) were included. Thirty-nine percent and 49% of women lived in countries with moderately-and highly-restrictive abortion laws, respectively. Women in countries with moderately-and highly-restrictive abortion laws were 0.62 (95% CI: 0.58, 0.65) and 0.88 (95% CI: 0.83, 0.93) times as likely to use modern contraceptives, respectively, compared to women in countries with broadly liberal abortion laws. However, in countries that had policies that supported adolescents to access contraceptives, women overall were more likely to use contraceptives. Liberalizing abortion laws and implementing policies that support women’s autonomy in contraceptive decision-making could enhance contraceptive use among women in SSA.